Upaya Meningkatankan Pemahaman Agama Islam Anak-Anak Mengaji Desa Pasir Permit Melalui Program GMB (Gerakan Mengaji Bareng) - Rahman Ritonga, Abdul; Samin Lubis, Mara; Khadijah, Siti; Wahyu Ningsih, Siti Nur (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Lack of care and resources is a serious problem for the children of Pasir Permit village. Moreover, Pasir Permit Village is a village that has just experienced expansion from Titi Putih Village, causing ideas, ideas and village budgets to become factors that inhibit the intelligence of Pasir Permit Village children. Therefore, there is a need for modern breakthroughs both from various internal and external parties in order to overcome the decline in the knowledge of Pasir Permit village children. This program aims to find out and improve the understanding of Pasir Permit village children in terms of Islamic religious knowledge through the joint recitation movement program, which includes learning to recite iqro and the Qur'an, learning to pray the funeral prayer and the practice of caring for prayer rooms and mosques. The GMB program (joint recitation movement) is carried out in the form of the KKN 19 UINSU program by teaching the children of Pasir Village permits directly through the talaqqi method, memorization and practice. The method used in this study is a qualitative method with primary data sources through observation, interviews and practical documentation. The results of this study found an increase in the ability of children in Pasir Permit Village's basic knowledge of Islam in the form of 5 times prayer, reading the Qur'an and the practice of funeral prayer.